Dynamics of Interocular Suppression in Amblyopic Children during Electronically Monitored Occlusion Therapy: First Insight. (2nd April 2016) - Kehrein, Stephan; Kohnen, Thomas; Fronius, Maria
ABSTRACT: Purpose : Interocular suppression is assumed to be the mechanism leading to impaired visual acuity, especially in strabismic amblyopia. Little is known about the dynamics of suppression during treatment. The aim of our study was to assess the development of the depth of suppression and its relation to changes in visual acuity during electronically monitored occlusion treatment. Methods : In a prospective pilot study, 15 amblyopes (8 with and 7 without strabismus) aged 5 to 16 years (mean 10.24 years) were examined before initiation of patching and then every 3 to 6 weeks for 4 months. To quantify suppression, a red filter ladder (Sbisa bar) was used, attenuating the image of the dominant eye until the patients reported a binocular perception (diplopia, rivalry, color mixture) or a change in eye dominance. Acuity was assessed with crowded Landolt rings. Daily occlusion was recorded using occlusion dose monitors. Results : The depth of interocular suppression showed a biphasic change: it increased significantly during the first month ( P =0.02), while visual acuity improved (mean 0.14 log units ±0.13; P <0.01). During the following 3 months, median suppression decreased back to the initial values. This reduction in suppression was more pronounced in anisometropic patients without strabismus than in amblyopes with strabismus. The average visual acuity steadily improved ( P <0.01) during the 4 months of treatment. Mean recorded patching dose rate was 3.91 h/d. The correlation between mean daily occlusion and suppression changes was not statistically significant. Conclusions : This first insight into the functional changes during electronically monitored patching suggests a complex relationship between visual acuity and interocular suppression that seems to be influenced by the presence of strabismus. Knowledge of the dynamics of interocular suppression is crucial for enhancing the outcome of occlusion treatment and also for the evaluation of its future role compared to emerging dichoptic treatments.